Associations between basic physiological observations recorded pre-thrombectomy and functional outcome: a systematic review and meta-analysis - Lumley, Hannah A.; Shaw, Lisa; Morris, Julia; Alton, Abi; White, Phil; Ford, Gary A.; James, Martin; Price, Christopher (Frontiers in Stroke, 2023)
Introduction Mechanical thrombectomy results in more favourable functional outcomes for patients with acute large vessel occlusion (LVO) stroke. Key clinical determinants of thrombectomy outcome include symptom severity, age and time from onset to treatment, but associations have also been reported with baseline physiological observations including systolic/diastolic blood pressure (SBP/DBP), blood/serum glucose, atrial fibrillation and conscious level. As these items are routinely available during initial emergency assessment, they might help to inform early prehospital and hospital triage decisions if evidence consistently shows associations with post-thrombectomy outcome. We undertook a meta-analysis of studies reporting pre-thrombectomy physiological observations and functional outcome. Method PRISMA guidelines were followed to search electronic bibliographies, select articles and extract data. Medline, PubMed, Cochrane HTA, Cochrane Central and Embase were searched. Included articles were observational or interventional thrombectomy studies published between 01/08/2004-19/04/2023 reporting 3-month modified Rankin Scale, split as favourable (0-2) and unfavourable (3-6). A modified version of the Quality in Prognostic Studies (QUIPS) tool was used to assess risk of bias. RevMan 5 was used to calculate Inverse Variance with Weighted Mean Differences (WMD) and Mantel-Haenszel Odds Ratios (OR) for continuous and categorical factors respectively. Results 37 studies were eligible from 8,687 records. Significant associations were found between unfavourable outcome and higher blood/serum glucose as a continuous (WMD=1.34mmol/l (95%CI 0.97 to 1.72);19 studies; n=3122) and categorical (OR=2.44 (95%CI 1.9 to 3.14) variable; 6 studies; n=5481), higher SBP (WMD=2.98mmHg (95%CI 0.86 to 5.11); 16 studies; n=4400), atrial fibrillation (OR=1.48 (95%CI 1.08 to 2.03); 3 studies; n=736), and lower Glasgow Coma Scale (WMD=-2.72 (95%CI -4.01 to -1.44); 2 studies; n=99). No association was found with DBP (WMD=0.36mmHg (95%CI -0.76 to 1.49); 13 studies; n=3614). Conclusion Basic physiological observations might assist early triage decisions for thrombectomy and could be used in combination with other information to avoid futile treatment and ambulance transfers. It is important to acknowledge that data were only from thrombectomy treated patients in hospital settings and it cannot be assumed that the predictors identified are independent or that modification can change outcome. Further work is needed to establish the optimal combination of prognostic factors for clinical care decisions.